THE INFLUENCE OF PSYCHOSOCIAL FACTORS ON THE DEVELOPMENT OF ISCHEMIC HEART DISEASE AND ACUTE CORONARY SYNDROME - K. G. Kozhokar; I. A. Urvantceva; K. Yu. Nikolaev (Кардиоваскулярная терапия и профилактика)
Since the end of the 20th century, as by the results of epidemiological studies, there is broadly known concept of risk factors (RF), having become the fundamentals of cardiovascular prevention. Traditionally, there is distinction of conventional and non-conventional, or psychosocial, RF, among those emotional factors and chronic stressors. The impact of non-conventional RF on the diseases development, and primarily cardiovascular, is questionned, but is the most actual due to high mortality from cardiovascular diseases, and one of the most complicated as well. The article focuses on a review of known studies of the influence of non-conventional RF on the ischemic heart disease development, and an attempt is done to evaluate the influence of these factors on the development of acute coronary syndrome.